Fabrication of a Canoe Hull with a Capacity of 6 People as a Means of Transportation in Swamp Waters in the Bagan Benio Area - Pardi, Pardi; Zulkarnain, Zulkarnain (ABEC Indonesia, 2024)
The water transportation route from Bagan Benio Hamlet, Tasik Serai Village, Talang Muandau District,Bengkalis Regency to Tarik Serai Village is via a small river which is very dependent on tidal conditions. Therefore, thehull shape that is suitable for this area is a flat hull model. In this research, a canoe hull design has been made withdimensions LoA = 5.5 m, B = 1 m, H = 0.35 m and T = 0.15 m with a passenger capacity of 6 people. The material usedis mangrove meranti wood. To strengthen and prevent water seepage, the outer hull is coated with fiberglass material.The fabrication process begins with forming the shape of the canoe body in accordance with the position of the tuskswhich are 0.5 m apart. After the body frame is formed according to the plan drawing, the next step is to install the bottomand side slab boards and provide jelcot between the boards to prevent leaks at the joints. After the hull is closed, the nextstep is to laminate the outer hull with a layer of Matt and Woven Roving which is evenly moistened with resin. Betweenthe Matt and Woven Roving layers, threaded nails are provided to strengthen the stickiness of the wood to the fiberglasslayer. After the bottom has been finished and finished, the boat body is turned over and the interior and seating facilitiesfor passengers are completed.